2008
DOI: 10.1111/j.1365-313x.2008.03492.x
|View full text |Cite
|
Sign up to set email alerts
|

Microalgal triacylglycerols as feedstocks for biofuel production: perspectives and advances

Abstract: SummaryMicroalgae represent an exceptionally diverse but highly specialized group of micro-organisms adapted to various ecological habitats. Many microalgae have the ability to produce substantial amounts (e.g. 20-50% dry cell weight) of triacylglycerols (TAG) as a storage lipid under photo-oxidative stress or other adverse environmental conditions. Fatty acids, the building blocks for TAGs and all other cellular lipids, are synthesized in the chloroplast using a single set of enzymes, of which acetyl CoA carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

76
2,334
6
55

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 3,257 publications
(2,535 citation statements)
references
References 121 publications
76
2,334
6
55
Order By: Relevance
“…The oil droplets in Scenedesmus NJ-1 may also serve as a reserve of energy in the form of TAGs. It has been reported that the contents of lipids and TAGs can be affected by nutrient stress, growth phases and/or the aging of cultures (Hu et al 2008b). In this study, large amounts of TAGs accumulated at the late phase of batch culture with low concentration of nitrogen.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…The oil droplets in Scenedesmus NJ-1 may also serve as a reserve of energy in the form of TAGs. It has been reported that the contents of lipids and TAGs can be affected by nutrient stress, growth phases and/or the aging of cultures (Hu et al 2008b). In this study, large amounts of TAGs accumulated at the late phase of batch culture with low concentration of nitrogen.…”
Section: Discussionsupporting
confidence: 49%
“…Therefore, lipids from Phase II (with 78 % NL) might be good feedstock for biodiesel production. The significant decrease in GL and PL contents of the Phase II cells may be attributed to the long exposure to nitrogen starvation, which stimulated hydrolysis of GL and PL and converted these polar lipids into NL (Hu et al 2008b). In Scenedesmus obliquus, the highest lipid productivity was achieved by pre-culture in glucose-supplemented medium before it was transferred to the media deficient in nitrate and phosphate (Mandal and Mallick 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…N, phosphorus) induces the formation of triacylglycerol‐rich lipid droplets coincident with an arrest in growth (Hu et al ., 2008; Yu et al ., 2009). Silicon is required for cell wall synthesis and growth in most diatoms, and silicon starvation also induces growth arrest and the formation of lipid droplets (Shifrin & Chisholm, 1981; Roessler, 1988; Traller & Hildebrand, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…4−6 Hu et al (2008) projected a possible yield of 200 barrels of oil per hectare (2.47 acres) of land used for growing photosynthetic algae. 5 This theoretical maximum algae yield is 100 times greater than that for soybeans, a commonly used feedstock for biodiesel, and is greater than any demonstrated yield (by a factor of 10−20), but should be a goal for the rapidly developing algae industry. 5 Algae-based biofuel production has a number of potential advantages:…”
mentioning
confidence: 99%